Some E-J Generalized Hausdorff Matrices Not of Type 𝑀 - T. Selmanogullari; E. Savaş; B. E. Rhoades (Abstract and Applied Analysis)
We show that there exists a regular E-J generalized Hausdorff matrix which has no zero elements on the main diagonal and which is not of type 𝑀 and establish several other related theorems.